2015
DOI: 10.1111/ibi.12311
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, seasonal and individual variation in the diet of White‐tailed Eagles Haliaeetus albicilla assessed using stable isotope ratios

Abstract: Many raptor species are considered to be generalists, taking a range of prey species. However, longitudinal dietary records are often scarce, although necessary for characterizing niche width of species at population and individual levels. Quantifying raptor diets at large spatio-temporal scales is often necessary for refining conservation efforts, although it can be particularly difficult and may involve a great effort by conventional means. Therefore, we adopted the analysis of stable isotopes in tissues of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 62 publications
(82 reference statements)
0
32
0
2
Order By: Relevance
“…, Nadjafzadeh et al . ). Our analyses suggested that the reproductive performance of individual breeding pairs decreased with reduced availability of water bodies in their vicinity.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…, Nadjafzadeh et al . ). Our analyses suggested that the reproductive performance of individual breeding pairs decreased with reduced availability of water bodies in their vicinity.…”
Section: Discussionmentioning
confidence: 97%
“…Stable isotope analyses showed that in north‐east Germany, aquatic organisms contribute 73% to the diet of the White‐tailed Eagle in winter and 91% in summer (Nadjafzadeh et al . ). Therefore, in our study population aquatic organisms constitute the primary food resource of the species during the breeding season.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Key words: age cohorts, Aquila chrysaetos, camera trap, latitudinal variation, wintering behavior Over the course of a full annual cycle, animals may change their foraging behavior (Dearing 1997), diet (Nadjafzadeh et al 2016), movement strategies (Newton 2007), space use (Sumasgunter et al 2016), energy budget (Czenze et al 2017), gonad size and sexual behavior (Gill 2006), and brain size, cranial morphology, and metabolic rate (L azaro et al 2017). This variation is often driven by seasonal fluctuations in either resource availability or reproductive physiology.…”
Section: Introductionmentioning
confidence: 99%